The Effect Of Halal Product Process Assistance Training (P3H) On Work Readiness Through Human Resources Competencies : (Study on Alumni Participants of P3H HCCM Training) - Fitria, Ramadhan; Sutomo; Suminar, Lintang; Handayani, Sari; Nafisah, A’isy Fiklil (PT Maju Malaqbi Makkarana, 2025)
The implementation of Law No. 33 of 2014 concerning Halal Product Assurance has driven an urgent need for competent halal assistants to support the national halal certification program. This study aims to analyze the effect of Halal Product Process Assistant (P3H) training on alumni's job readiness with HR competency as a mediating variable. The phenomenon in the field shows that although Indonesia has the largest Muslim population in the world, the readiness of halal assistant human resources is still not optimal, where a survey by the Ministry of Religious Affairs (2023) indicated that only 45% of halal assistants have adequate job readiness. This study uses a quantitative approach with an explanatory research design, involving 160 respondents who are alumni of the P3H Halal Center Cendekia Muslim training for the 2022-2025 period who were selected through simple random sampling from a population of 230 alumni. Data were collected using a questionnaire with a 5-point Likert scale and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS 3.3.3 software. The results of the study showed that P3H training had a significant effect on work readiness (β = 0.038; t-value = 4.330; p-value = 0.041) and HR competency (β = 0.138; t-value = 5.029; p-value = 0.009). HR competency had a significant effect on work readiness (β = 0.230; t-value = 3.355; p-value = 0.001). Furthermore, HR competency was proven to mediate the effect of P3H training on work readiness (β = 0.032; t-value = 5.900; p-value = 0.037). The research model showed an R² value of 0.019 for HR competency and 0.057 for work readiness, with a Q² value of 0.745 indicating good predictive relevance. These findings confirm that human resource competency plays a partial mediator in the relationship between P3H training and job readiness, in accordance with Kirkpatrick's Four-Level Training Evaluation Model of human resource development theory. This study provides a theoretical contribution by integrating human resource management theory and job readiness within the context of the Indonesian halal ecosystem, as well as a practical contribution in the form of recommendations for developing a more applicable P3H training curriculum to support the government's target of achieving 100% halal-certified products by 2029.